O falar sertanejo na voz de Patativa do Assaré: a representação de uma identidade linguística e social - Ferreira Neto, Raimundo José (2022)
The Portuguese language spoken in Brazil is marked by the diversity that also characterizes its people and culture. For this reason, despite its adoption as an official language, the language used in the country presents variations at the most diverse levels of analysis, which demonstrates the relevance of the sociolinguistic study. In this scenario, popular literature from Ceará has Patativa do Assaré as a representative name of its production, identified, among many other factors, by the language it uses. Despite being the object of several studies, we verified, through the state of the art, that there are still analytical perspectives to be applied to the author's production. In view of the above, our general objective is to describe the representation of a linguistic and social identity from the linguistic variations observed in the countryside speech of Patativa do Assaré. Therefore, we seek theoretical support in variationist sociolinguistics (LABOV, 2001, 2008 [1972]; CALVET, 2002; ARAGÃO 1999, 2013; MOLLICA, 2020; COELHO et al 2021), considering the phonetic-phonological levels as an analytical scope (ALENCAR, 1997; ROBERTO, 2016; SEARA, NUNES, LAZZAROTTO-VOLCÃO, 2019; CRISTÓFARO SILVA, 2021) and morphosyntactic (SCHERRE, NARO, 1998; MENDES, OUSHIRO, 2015; AZALIM et al 2018). In addition, we also analyze the representation of an identity from the theoretical bias adopted (HALL, 2006; KIESLING, 2013; OUSHIRO, 2019). The methodological design indicates that it is a basic, descriptive and mixed research, since it adopts both a quantitative and qualitative approach. In turn, the procedures performed classify it as bibliographic research. The sample is composed of 15 poems collected, based on previously defined criteria, in the works Inspiração Nordestina (2003 [1956]), Cante lá que eu canto cá (2014 [1978]) and Ispinho e Fulô (2012 [1988]). From the analyzes carried out, it is concluded that there are phonetic-phonological variations of different types in countryside speech from Patativa do Assaré, with those characterized by the loss of phonetic segments being more recurrent, especially the apocope. At the morphosyntactic level, we found that linguistic variations occur more frequently in cases of nominal agreement, to the detriment of cases of verbal agreement. Finally, the results demonstrate a strong link between the author and the countryside and social identity, which proves the use of the respective linguistic variety as a resource that aims to give voice to marginalized people, thus evidencing their needs and claiming better living conditions for them the said groups.